Clinical effectiveness of a digitally delivered balance program for older adults: a nonrandomized controlled trial - Folasade Phillips; Sandhya Yadav; Cynthia Castro Sweet; Rachel NS Foster Kirk; Mindy Hong; Samuel Mink; Jeffrey Krauss (Journal of Comparative Effectiveness Research, 2026)
Aim: To evaluate the clinical effectiveness of a digitally delivered balance program relative to an attention-control comparison group in older adults at risk for falls. Materials & methods: This nonrandomized controlled trial recruited adults aged 65 years and older with moderate-to-high fall risk. Participants were assigned to a digital balance program (exercise therapy, education and health coaching) or an attention-control group (education materials). Outcomes were assessed via self-report surveys at baseline and 3 months. Analyses including all assigned participants evaluated changes in fall rate, fall severity, physical function and medical care utilization. Results: A total of 687 participants were included in the analysis (intervention: n = 344; attention-control: n = 343). The mean age was 68.8 years, and 74.1% of participants were female. In the primary analysis, adjusting for baseline factors, the intervention group demonstrated a 37% lower fall rate compared with the attention-control group at 3 months (IRR: 0.63, 95% CI: 0.48–0.82, p < 0.001). The intervention group also demonstrated significant improvement in physical functioning (β = 6.86, 95% CI: 3.80–9.92, p < 0.001) and lower odds of emergency department visits (OR: 0.43, 95% CI: 0.24–0.76, p = 0.004). Intervention participants engaged in an average of 25.2 exercise therapy sessions over the 12-week period. Conclusion: Findings suggest that participation in the digital balance program was associated with reductions in self-reported fall rates, improvements in self-reported physical function, and lower odds of emergency department utilization. High engagement levels further indicate that digitally delivered programs offer a viable option for improving health outcomes in this population. Trial Registration: Clinicaltrials.gov NCT06868680 retrospectively registered 6 March 2025.